IMPROVING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT BY USING RECIPROCAL TEACHING TECHNIQUE - Julaisa, .; Sada, Clarry; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This research was conducted to investigate whether reciprocal teaching technique improves reading comprehension of tenth grade students of SMA Islamiyah Pontianak in Academic Year 2015/2016 in reading narrative text or not.The research method was pre-experimental study with intact group comparison. The sample of this research divided into two groups: experimental group that consist od 30 students and control group that consist of 30 students. Based on the result of post-test between experimental group and control group, there was different significant achievement. The mean score ofÂ post-test of experimental group higher than control group (89.83 > 66). In addition, the t-test score (7.64) was higher than t-table (2.045) at 0.05 the degree of freedom (df)= N-1 (30-1=29) and the result of effect size is 1,93 where the catagory is strong effect.Furthermore, the null hypothesis (Ho) was rejected. Because t-value > t-table (7.64 > 2.045) on the level of significance 0.05 and the alternative hypothesis (Ha) was accepted. Keywords : Reciprocal Teaching Technique, Reading Comprehension, Narrative text. Abstrak: Penelitian ini dilakukan untuk menginvestigasi apakah teknik reciprocal teaching meningkatkan pemahaman membaca siswa kelas sepuluh SMA Islamiyah Pontianak pada tahun ajaran 2015/2016 dalam membaca teks naratif atau tidak. Metode penelitian yang digunakan adalah penelitian pre-eksperimen dengan intact group comparison. Sample penelitian ini terbagi menjadi dua kelompok yaitu 30 siswa kelompak eksperimen dan 30 siswa kelompok control. Berdasarkan dari hasil post-test antara kelompok eksperimen dan kelompok control terlihat berbedaan nilai yang signifikan. Nilai rata-rata post-test kelompok ekperimen lebih tinggi dari kelompok control (89.83 > 66). Ditambah lagi, nilai dari t-test (7.64) lebih tinggi dari t-table (2.045) pada tingkat kesalahan 0.05 dengan df =N-1 (30-1-29) dan hasil dari besar pengaruhnya adalah 1.93 yang mana dikategorikan memiliki pengaruh yang sangat kuat. Oleh karena itu, null hypothesis (Ho) dari penelitian ini ditolak karena nilai t > t-table (7.64 > 2.045) dan alternative hypothesisnya diterima. Kata kunci : Teknik Reciprocal Teaching, Pemahaman Membaca, Teks Naratif. Â